Simultaneous Bio-oxidation and Bio-reduction of Chlortetracycline and Paracetamol Using a Sequenced Batch Reactor (SBR) - Celik, Aytekin (Wiley-V C H Verlag Gmbh, 2022)
Chlortetracycline (CTC) and paracetamol (PCT), which are among the most widely used drugs today, have started to be detected in groundwater and surface waters. For this reason, water resources are exposed to more and more drug pollution every day. For this purpose, it is important to remove these pollutants from the environments where they are located. In this study, CTC and PCT drugs together with ammonium (NH4-N) and nitrate (NO3-N) pollutants were simultaneously removed in a single reactor. At the end of the study, PCT and CTC were removed at maximum 99.8 % and 66 % under the same conditions, respectively. At the same time, nitrification and denitrification efficiency were obtained as 99 %. In terms of volumetric removal flux, chlortetracycline and equivalent O-2 flux of chlortetracycline maximum were calculated as 2.05 and 3.56 mg/L.d. Likewise, the maximum removal volumetric flux of paracetamol and its O-2 equivalent flux were determined as 136 and 301.5 mg/L.d. The results showed that, aerobic nitrified bacteria preferred paracetamol rather than chlortetracycline. In other words, nitrified bacteria preferred paracetamol/chlortetracycline as the second electron acceptor after O-2. As a result, chlortetracycline and paracetamol were successfully eliminated in the SBR system. In addition, simultaneous biological removal of these drugs with nitrogenous pollutants has been successfully achieved.
Keywords: Chlortetracycline; Paracetamol; Pharmaceuticals; Sequenced Batch Reactor; Volumetric Flux